Multiple uses of water by users granted in the hydrographic basins of the aguapeí and peixe rivers - da Silva, Fernanda Buono [UNESP]; Queiroz, Timóteo Ramos [UNESP]; Burkert, Denilson; Manzione, Rodrigo Lilla [UNESP] (Revista Brasileira de Geografia Fisica, 2021)
The growing demand for water resources can generate conflicts between different users. To this end, water resources management instruments were implemented, in particular the granting of the right to use, which prioritize the multiple and rational use of water. The work was carried out with the objective of analyzing the profile and the distribution of water uses granted in relation to socioeconomic aspects in the municipalities that make up the Hydrographic Basins Committee of the Aguapeí and Peixe Rivers (CBH-AP). Grant data from 58 municipalities with which descriptive statistics were analysed and prepared for the discussion on the scenario of the multiple uses of water granted. Subsequently, the data were given to the multiple regression statistical analysis, in which the relationship between the number of grants per municipality and its socioeconomic parameters was analyzed. The results demonstrated the grants in the municipalities that comprise an area covered by the Hydrographic Basins Committee of the Aguapeí and Peixe rivers are mainly related to the use of groundwater in rural areas. In the three municipalities (Bastos, Dracena and Tupã) concentrate 26% of the analyzed grants. The increase in MHDI and population, at the same time, stimulates the growth in the number of grants. Thus, there is a need to implement public policies that collaborate directly or indirectly to increa se the regularization of water use.
Usos múltiplos da água por usuários outorgados nas bacias hidrográficas dos rios aguapeí e peixe
Keywords: Freshwater; Public Policy; Streamflow region alization; São Paulo western; Water governance; Water resource